Assessing Vocabulary Using Technology: Literature Review - THEA KARUNI RESPATI (International Islamic Schools Alliance, 2024)
The purpose of this study is to investigate how vocabulary evaluation using Quizziz affects language understanding in elementary school pupils. A descriptive qualitative methodology is included in the process, together with data analysis from the assessment findings and observation. The research strategy used in this study was phenomenology. The findings demonstrated that students' interest and motivation in learning vocabulary were considerably raised by utilizing Quizziz. Assessment scores have improved, indicating that students are making significant progress in their comprehension and application of new language. Positive learning environments are further enhanced by the platform's competitive and participatory environment. These results show that Quizziz is a useful tool for raising vocabulary comprehension levels and promoting student participation in language learning. To produce more interesting and significant learning experiences, this research suggests using technology in language learning even more.